Mechanisms linking river flow regime and riparian hardwood establishment - Steven F. Railsback; John H. Bair (Ecosphere)
Abstract The dominant conceptual model for how river flow affects when and where riparian hardwood trees establish (the “recruitment box model”) considers streamflow recession and a survivable rate of stage decline to predict survival of seedling desiccation. However, to become established, plants must also survive the pre‐seedling life stages and avoid inundation and scour mortality in high flows. We examine the relative importance of these flow‐dependent mechanisms by representing them in a two‐dimensional simulation model. Analysis of the model as applied to a low‐gradient reach of a large mountain river indicates that the soil characteristic determining moisture elevation (the “capillary fringe” height) is the most important process driving establishment rates; also important are the dates of seed deposition, inundation mortality, and the time needed for sprouted seeds to develop roots. Root growth rate had only moderate effect on seedling survival. These results indicate that the conventional conceptual model of establishment is incomplete. At our site, natural rates of decline in soil moisture elevation exceeded root growth rates, so widespread establishment required periods of near‐steady flows. Further, under both reservoir‐controlled and unimpaired flow regimes, establishment was strongly determined by post‐deposition flow increases: seeds deposited at elevations low enough to support rooting were often killed via inundation or scour in flow fluctuations that occurred under both reservoir‐regulated and unregulated flow scenarios. When soil moisture dynamics are represented even simply, the survivable rate of stage decline is not constant but depends on capillary fringe height, seed elevation, and the duration of stage decline. A more complete conceptual model of hardwood establishment considers that seeds need to be deposited where soil is moist long enough to develop roots but far enough from the water's edge to avoid mortality in flow fluctuations; for soil moisture to remain within reach of roots, which could require unusually steady flows, a high capillary fringe, or favorable groundwater gradients; and to avoid mortality due to scour or inundation in winter high flows. Model sensitivity and lack of literature suggest the time and moisture requirements for seeds to develop roots and inundation mortality of seedlings as research priorities.